2021
DOI: 10.3390/brainsci11010108
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Onset Muscle Soreness (DOMS): The Repeated Bout Effect and Chemotherapy-Induced Axonopathy May Help Explain the Dying-Back Mechanism in Amyotrophic Lateral Sclerosis and Other Neurodegenerative Diseases

Abstract: Delayed onset muscle soreness (DOMS) is hypothesized to be caused by glutamate excitotoxicity-induced acute compression axonopathy of the sensory afferents in the muscle spindle. Degeneration of the same sensory afferents is implicated in the disease onset and progression of amyotrophic lateral sclerosis (ALS). A series of “silent” acute compression proprioceptive axonopathies with underlying genetic/environmental factors, damaging eccentric contractions and the non-resolving neuroinflammatory process of aging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
161
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(164 citation statements)
references
References 139 publications
(186 reference statements)
3
161
0
Order By: Relevance
“…It is demonstrated that dual-task (cognitive and gait functions are used at the same time) could induce a more significant stress in the form of an acute stress response and could impair proprioception leading to falls, compared to single task in the elderly [ 35 ]. The author of this paper further suggest that the same result could occur in unaccustomed or strenuous athletic moments when force production is depleted, but cognitive demand derived ASR is induced in order to sustain athletic performance [ 27 , 30 ]. It is important to note, that this translation applies only to the relationship between cognitive demand induced ASR and proprioception in force production depleted dual-task moments, and not on the fall of elderly which is a multifactorial construct.…”
Section: Hypothesis: Nc-acl Injury Is Caused By Acute Compression Axonopathy Followed By a Harsher Secondary Damage Including The Injury mentioning
confidence: 99%
See 4 more Smart Citations
“…It is demonstrated that dual-task (cognitive and gait functions are used at the same time) could induce a more significant stress in the form of an acute stress response and could impair proprioception leading to falls, compared to single task in the elderly [ 35 ]. The author of this paper further suggest that the same result could occur in unaccustomed or strenuous athletic moments when force production is depleted, but cognitive demand derived ASR is induced in order to sustain athletic performance [ 27 , 30 ]. It is important to note, that this translation applies only to the relationship between cognitive demand induced ASR and proprioception in force production depleted dual-task moments, and not on the fall of elderly which is a multifactorial construct.…”
Section: Hypothesis: Nc-acl Injury Is Caused By Acute Compression Axonopathy Followed By a Harsher Secondary Damage Including The Injury mentioning
confidence: 99%
“…We argue that the concomitant burst compression or crush of the axons of the fastest conducting sensory neurons of the periosteum and epiphysis by the same damaging force could contribute to the impairment of proprioception. It should not be forgotten that the proposed signaling, that highlights excessive eccentric force generation by an ASR [ 27 , 30 ], is bone derived as well, and is demonstrated in the form of immediate release of circulating osteocalcin [ 40 ].…”
Section: Hypothesis: Nc-acl Injury Is Caused By Acute Compression Axonopathy Followed By a Harsher Secondary Damage Including The Injury mentioning
confidence: 99%
See 3 more Smart Citations